The amount and speciation of trace elements transported from rice field to canal during a flooding event - Trinh, Ha Thu; Duong, Hanh Thi; Struwe-Voscul, Ann-Christin; Strobel, Bjarne W.; Giang, Le Truong (Vietnam Journal of Science and Technology, 2019)
Trace element pollution of soils, sediments and surface water can pose a risk for the local population and the environment of Vietnam. Rice fields can be affected by storm events, which cause the release of trace elements into surface water and transport them into drinking wells. The aim of this study was to investigate if dissolved and suspended As, Pb and Zn concentrations in surface water of a paddy rice fields and an irrigation canals increased during a flooding event and exceed the Vietnamese Surface Water Quality Standards and WHO Guidelines for Drinking-water Quality. The study site is a rice field area in the Thanh Hoa province in Central Vietnam, which experiences an average of 2.4 storms every year causing overflow of streams and low-order canals. Concentrations of As increased during the flooding event with dissolved As being the prevailing fraction, which followed a late flush behavior. Lead showed no significant difference in concentration over time. Zn concentrations only increased significantly in the canal upstream the field in the morning of the first day. Suspended Zn dominated at that time, following the first flush behavior of TSS concentrations. Concentrations of As, Pb and Zn did not exceed the Vietnamese Surface Water Quality Standards or WHO Guidelines for Drinking-water Quality at any time and they are therefore of no concern for the health of the local population